2020
DOI: 10.1039/d0ra03221b
|View full text |Cite|
|
Sign up to set email alerts
|

Metal-free oxidative coupling of arylmethylamines with indoles: a simple, environmentally benign approach for the synthesis of 3,3′-bis(indolyl)methanes

Abstract: The efficient metal-free oxidative coupling of arylmethylamines with indoles has been developed using molecular oxygen as a green oxidant towards a novel rout of 3,3′-bis(indolyl)methanes (BIMs) synthesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…Although these synthetic strategies are present, there are some limitations among them. In the last few years, benzylamines have increased attention as substrates for designing a variety of nitrogen‐containing heterocycles [10–12] . In recent times, there are many reports for synthesis of oxazoles with great substrate scope using benzylamines and the starting materials having functionality such as 1,2‐dicarbonyls, 1,3‐dicarbonyls, α‐bromo ketones, aldehydes, ketones, alkynes, alkenes and chalcones.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although these synthetic strategies are present, there are some limitations among them. In the last few years, benzylamines have increased attention as substrates for designing a variety of nitrogen‐containing heterocycles [10–12] . In recent times, there are many reports for synthesis of oxazoles with great substrate scope using benzylamines and the starting materials having functionality such as 1,2‐dicarbonyls, 1,3‐dicarbonyls, α‐bromo ketones, aldehydes, ketones, alkynes, alkenes and chalcones.…”
Section: Introductionmentioning
confidence: 99%
“…In the last few years, benzylamines have increased attention as substrates for designing a variety of nitrogen-containing heterocycles. [10][11][12] In recent times, there are many reports for synthesis of oxazoles with great substrate scope using benzylamines and the starting materials having functionality such as 1,2-dicarbonyls, 1,3dicarbonyls, α-bromo ketones, aldehydes, ketones, alkynes, alkenes and chalcones. In this context, the present review article aims to assess the work reported on recent developments in the oxazole synthesis from benzylamines via CÀ H/ CÀ N bond functionalization.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the development of catalytic system under molecular oxygen or air as oxidant has been an increasing attention in the aerobic oxidation reactions development. [42][43][44][45][46][47][48][49][50] Traditionally, the Debus-Radziszewski imidazole synthesis meth-od is used to synthesize imidazoles by the carbonyl compounds and ammonium salts condensation. The different synthetic methods have been reported for preparation of trisubstituted imidazoles from isocyanides, nitriles, amino acids, imines, amides, and amidines substrates.…”
Section: Introductionmentioning
confidence: 99%
“…The importance of economic viability and nature balance means the development of environmentally benign, simple and fast protocols for synthesis of polysubstituted imidazoles still has signicant scope. To continue efforts towards synthesis of nitrogen containing heterocycles, [32][33][34][35][36] herein we are going to report an alternative simple and efficient method for the synthesis of polysubstituted imidazoles.…”
Section: Introductionmentioning
confidence: 99%